Dry Powder Coating using Planetary Centrifugal Mixer - Yasunori Miyazaki; Kaoru Miyawaki; Tomonobu Uchino; Yoshiyuki Kagawa (Frontiers Media S.A., 2015)
Purpose: Extemporaneous compounding is an important part of pharmacy practice, and should be standardized and sophisticated to ensure the quality of the compounded preparations. Recently, we applied a planetary centrifugal mixer (PCM) to powder blending, which has attracted interest for its small scale and lack of contamination. In this study, we aimed to reveal the feasibility of dry powder coating through ordered mixing of fine particles using PCM. Methods: Cohesive lactose powders (Pharmatose450M) were dry coated with magnesium stearate (MgSt) using from 0.1 to 5%(w/w) content. The operational variables tested were operation time (1-30 min), operation speed (400-1000 rpm), vessel size (24-100 mL), and charging rate in the vessel (20-40%). The processed powders were evaluated for their surface morphology, flowability, and wettability. Furthermore, fine ibuprofen particles were coated with various lubricants, and then the dissolution profiles were examined. The crystallinity of ibuprofen was assessed using FT-IR and PXRD. Results: Lactose powders were successfully coated with MgSt using PCM. When the level of MgSt was over 1%, the surface of the lactose powders was thoroughly covered. Angles of repose were 51° and 41° for unprocessed and processed powders with 1% MgSt, respectively. The contact angle of the water drop on the 1% MgSt sample leached to be 132°, changing to a hydrophobic surface. Investigations under various operational conditions revealed that higher improvement was observed upon higher speed and longer time, and a smaller charging rate in the vessel. Vessel size had no impact. Moreover, improved dissolution of ibuprofen coated with both hydrophilic and hydrophobic lubricants was observed owing to good dispersing behavior. Besides, no alteration of crystallinity was detected. Conclusions: PCM is an effective tool for dry powder coating with low impact stress. The presented method will contribute a great deal to making crushed tablets a functional powder.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.